Associations Between Dysfunctional Thoughts, Leisure Activities, and IL-6 in Caregivers of Family Members With Dementia. Issue 2 (24th February 2023) - Vara-García, Carlos; Romero-Moreno, Rosa; Barrera-Caballero, Samara; Pedroso-Chaparro, María del Sequeros; Jiménez-Gonzalo, Lucía; Olazarán, Javier; Mausbach, Brent; von Känel, Roland; Losada-Baltar, Andrés
ABSTRACT: Objective: Dementia caregiving is associated with negative physical health consequences, including inflammation processes. The objective of this study was to analyze the associations between dysfunctional thoughts, frequency of leisure activities, and interleukin 6 (IL-6) in a sample of dementia family caregivers. Methods: One hundred forty dementia caregivers participated in this cross-sectional study. The relationships among caregivers' dysfunctional thoughts, leisure activities, and IL-6 were adjusted for demographic characteristics, stressors, and physical and mental health indicators in a linear regression analysis. Results: Higher levels of dysfunctional thoughts ( t = −2.02, p = .045) were significantly associated with lower frequency of leisure activities. In turn, lower frequency of leisure activities was significantly associated with higher levels of IL-6 ( t = −2.03, p = .045). Dysfunctional thoughts were no longer significantly associated with IL-6 levels when both dysfunctional thoughts and leisure activities were included in the same model ( t = 1.78, p = .076). A significant indirect effect was found for the association between higher levels of dysfunctional thoughts and higher levels of IL-6 (standardized indirect effect = 0.036, bootstrap standard error = 0.026, 95% confidence interval = 0.0001–0.1000) through its association with fewer leisure activities. Conclusions: Our findings suggest that the direct effect of caregivers' dysfunctional thoughts on IL-6 may be mediated by the impact on caregivers' frequency of leisure activities. Results suggest that training caregivers in reducing dysfunctional thoughts to thereby increase leisure activities may be useful in reducing inflammation.